Three species of dominant plant parasitic nematodes associated with banana plants in Yogyakarta Special Region Province, Indonesia - Nurlaili N. A.; Indarti S.; Putra N. S.; Soffan A. (Helminthologia)
Plant parasitic nematodes (PPNs) are one of the most important pests on banana plantations. This research was conducted to identify the dominant PPNs species threat in banana cultivation. The purposive sampling method was performed in banana plantations to collect the roots of banana plants and the soil around them to extract the nematodes. Nematode identification was carried out morphologically, morphometrically, and molecularly using the primer pair D2A/D3B. The highest population of PPNs from root and soil sample (respectively) in Turi were Radopholus (84 nematodes/10 gram root) and Helicotylenchus (37.3 nematodes/100 mL soil), in Kasihan were Pratylenchus (181.3 nematodes/10 gram root) and Meloidogyne (53.3 nematodes/100 mL soil), while in Jetis were both Helicotylenchus with population of 480 nematode/10 gram root and 120 nematode/100 mL soil. Phylogenetic analysis placed the population of R. similis from Turi, Yogyakarta in a monophyletic clade with R. similis from Tanzania, China, and Colombia. The Kasihan, Yogyakarta population of P. coffeae was placed in a monophyletic clade with P. coffeae from China and Tanzania. Additionally, the Jetis, Yogyakarta population of H. multicinctus was separated from H. multicinctus populations from Nigeria, China, Sudan, Vietnam, Brazil, India, Florida, Greece, and Colombia. These results could be used as the database of morphological, morphometric, and molecular characteristics of nematode species in Indonesia and as a basis for future banana parasitic nematode management.